Iron microencapsulation with blend of gum arabic, maltodextrin and modified starch using modified solvent evaporation method – Milk fortification. (January 2015) - Gupta, Chitra; Chawla, Prince; Arora, Sumit; Tomar, S.K.; Singh, A.K.
Abstract: Iron microcapsules were prepared with blend of gum arabic, maltodextrin and modified starch using modified solvent evaporation method. Process parameters were optimized for obtaining maximum encapsulation efficiency and stability of microcapsules. Effect of different concentration of alcohol, different ratio of mixture to absolute alcohol, different composition of wall material and different amount of iron salt on the encapsulation efficiency (EE) of iron microcapsules were evaluated. Microcapsules prepared with gum arabic, maltodextrin and modified starch in the ratio of 4:1:1 and mixture to absolute alcohol ratio 1:10 showed maximum encapsulation efficiency (91.58%) and stability. External morphology of iron microcapsules revealed slightly circular structure with minimum cracks and dents on the surface. Particle size as analysed by inverted light microscope was in the range of 6.84–33.42 μm. Iron microcapsules were added to milk and evaluated for sensory characteristics and oxidative stability. Sensory scores of iron salt fortified milk were significantly lower ( P  < 0.05) as compared to iron microcapsules fortified milk during storage, however, this difference could be observed only upto the 5th day of storage. Iron microcapsules fortified milk showed significantly higher ( P  < 0.05) in-vitro bioavailability of iron as compared to control (unfortified) and iron salt fortified milk. Graphical abstract: Highlights: Gum arabic, maltodextrin and modified starch was suitable for microencapsulation. 1:10 ratio of mixture to absolute alcohol showed maximum EE. Morphological characteristics revealed slightly circular structure of microcapsules. Microcapsules fortified milk showed higher sensory scores and lower TBA value. Microcapsules fortified milk showed higher in-vitro iron bioavailability.